Chinese Industrial Policy in the New Energy Vehicles Industry - Levashenko, Egor; Stuchlíková, Zuzana, 1979-; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis delves into the Chinese Industrial Policy within the New Energy Vehicles (NEVs) sector, known as electric vehicles (EVs) in China, and its implications for industry growth, environmental sustainability, and economic advancement. Through an examination of policy evolution, incentives, and market dynamics from 2009 to 2022, the research sheds light on the complexities of NEV adoption and development in China. Utilizing frameworks such as PESTE, Porter's Five Forces, and SWOT analysis, the study offers insights into external and internal factors shaping the NEV industry landscape. Findings reveal the pivotal role of government support in driving NEV adoption, the multifaceted motivations behind consumer choices, and the competitive dynamics within the sector. Opportunities for growth, challenges, and the sustainability of NEVs as a mainstream transportation solution are explored, highlighting the need for continuous monitoring and informed decision-making to guide the industry toward environmental sustainability and consumer acceptance.
Vedoucí práce: Zuzana Stuchlíková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses